Enhancing education in electronic sciences using virtual laboratories developed with effective practices. Issue 2 (8th June 2011) - Garcia, I. A.; Pacheco, C. L.; Garcia, J. N.
ABSTRACT The aim of a Virtual Lab project is to provide students access via the Internet to various experiments in those Universities where the infrastructure resources are poor. Moreover, a Virtual Lab is based on a distance education concept due to the fact that certain students may be interested in studying even at places which are far away from University eliminating the necessity to be there in person. However, methodologies used in the development of this kind of educational applications have too many problems: a lack of common theoretical frameworks which can be used by anyone in the project, and excessive formality in both technical and pedagogical factors. So, considering these factors, the introduction of "effective practices" within an alternative methodology to develop this kind of software is proposed. The applications of the Virtual Lab have been tested with the students enrolled at Technological University of the Mixtec Region and the initial educational results of the implementation of the DCLab software are presented. © 2011 Wiley Periodicals, Inc. Comput Appl Eng Educ 22:283–296, 2014; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.20554